Educational Values in Al-Qur'an al-Ahzab Letter Verse 59 and al-Nur Verse 31 (Study of the Tafsir Al-Maraghi) - Fauziah, Siti Ulfah; Munandar, Didih Syakir (JPPI | Jurnal Penelitian Pendidikan Islam, 2018)
This study of texts with hermeneutical approaches found several important findings, that are the necessity of women to cover their genitals so that their purity is maintained and maintained. Women are also required to guard their views from objects that are forbidden by the scriptures, maintain purity, do not overdo it and use jewelry, and immediately repent when committing sins and mistakes.